Decentralized group decision making using blockchain - Singh M.; Baranwal G.; Tripathi A.K. (My University, 2025)
Group decision making (GDM) involving consensus reaching process (CRP) attempts to achieve a consensus among Decision-Makers (DMs) before coming to a final decision. Computer-based decision support systems are present to support the decision-making process called the Group Decision Support Systems (GDSS). The traditional GDSS being centralized is subject to security, transparency, and trust issues, such as vulnerable to security risks providing attackers with a single target to attack, a single point of failure, and biases. In this regard, this paper identifies and discusses such issues. To address these issues, we introduce a novel idea of a decentralized group decision-making structure using blockchain technology. We proposed a consensus model suitable for the blockchain platform. For validation, we implement the proposed work using the Ethereum blockchain. Furthermore, a theoretical security analysis of the proposed model is also done to validate that the system eliminates possible security attacks. The possible experiments show that the proposed work minimizes the gas cost by minimizing the feedback cost. To the best of our knowledge, this work is the first step toward introducing the idea, and the advanced approaches will be the natural consequences of this work. © 2023, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.